End-of-Kindergarten Spelling Outcomes: How Can Spelling Error Analysis Data Inform Beginning Reading Instruction? - Julia Ai Cheng, Lee; Al Otaiba, Stephanie (Taylor and Francis Inc., 2016)
In this study, we examined the spelling performance of 430 kindergartners, which included a high-risk sample, to determine the relations between end-of-kindergarten reading and spelling in a high-quality language arts setting. We described, analyzed, and compared spelling outcomes, including spelling errors, between good and poor readers. The findings suggest that not all of the children achieved the desired standard as outlined by the Common Core State Standards. In addition, not every good reader was a good speller, and not every poor speller was a poor reader. The study shows that spelling tasks that are accompanied by spelling error analysis provide a powerful window for making instructional sense of children’s spelling errors and for individualizing spelling instructional strategies